1990
DOI: 10.1113/jphysiol.1990.sp018107
|View full text |Cite
|
Sign up to set email alerts
|

Fast gating kinetics of the slow Ca2+ current in cut skeletal muscle fibres of the frog.

Abstract: SUMMARY1. Calcium currents and intramembrane charge movements were measured in cut twitch muscle fibres of the frog and the time course of activation of the current was studied using various conditioning pulse protocols.2. When a conditioning activation was produced by a depolarizing pulse which ended before inactivation occurred, a subsequent depolarization led to a faster onset of activation, indicating that the system had not completely returned to the initial state during the interval between the two pulse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
59
1

Year Published

1992
1992
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(67 citation statements)
references
References 40 publications
7
59
1
Order By: Relevance
“…In addition they permit an extremely slow calcium inward current (L_type current) whose physiological role is still unclear (for a review see Melzer et al 1995). L_type current characteristics have been extensively studied in adult amphibian and mammalian skeletal muscle (for references see Delbono, 1992;Feldmeyer et al 1990Feldmeyer et al , 1992Feldmeyer et al , 1995Garcia et al 1992;Francini et al 1996). On the other hand, important data on structure-function relationships of the channel have been obtained by heterologous expression of recombinant DHP receptors in cultured immature muscle cells (myotubes) (Tanabe et al 1988;Garcia et al 1994).…”
mentioning
confidence: 99%
“…In addition they permit an extremely slow calcium inward current (L_type current) whose physiological role is still unclear (for a review see Melzer et al 1995). L_type current characteristics have been extensively studied in adult amphibian and mammalian skeletal muscle (for references see Delbono, 1992;Feldmeyer et al 1990Feldmeyer et al , 1992Feldmeyer et al , 1995Garcia et al 1992;Francini et al 1996). On the other hand, important data on structure-function relationships of the channel have been obtained by heterologous expression of recombinant DHP receptors in cultured immature muscle cells (myotubes) (Tanabe et al 1988;Garcia et al 1994).…”
mentioning
confidence: 99%
“…Fg␣1S might encode the "fast" Ca 2ϩ channel. On the other hand, slowly activating Ca 2ϩ currents of frog muscle can be switched to a fast activation mode by prior depolarization (42,43). Therefore, the fast phase seen in the normal unconditioned current (and the currents induced here by Fg␣1S) may not correspond to a separate channel population but to a fraction of the slow channels showing fast gating kinetics in the steady state.…”
Section: Current-dependent Inactivation Of Expressed Channels-ltype Camentioning
confidence: 97%
“…After activation and subsequent deactivation of the current this channel can remain in a condition that allows more rapid opening showing that the channel exhibits at least two closed states with very different kinetics of voltage-dependent transition to the open state, i.e. a slow and a fast gating mode (Feldmeyer et al 1990).…”
Section: Feldmeyer and Othersmentioning
confidence: 99%
“…However, it has been shown that the activation kinetics of the skeletal muscle channel is accelerated following a conditioning prepulse (Feldmeyer, Melzer, Pohl & Z6llner, 1990;Ma, Hosey & Rios, 1992). After activation and subsequent deactivation of the current this channel can remain in a condition that allows more rapid opening showing that the channel exhibits at least two closed states with very different kinetics of voltage-dependent transition to the open state, i.e.…”
Section: Feldmeyer and Othersmentioning
confidence: 99%
See 1 more Smart Citation